2012
DOI: 10.1021/jf302583r
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Phenolic Content and Antioxidant Activity of Fermented Rooibos Herbal Tea Infusions: Role of Production Season and Quality Grade

Abstract: Data are required to calculate the dietary exposure to rooibos herbal tea flavonoids and phenolic acids. Representative content values for the principal phenolic compounds and total antioxidant capacity of fermented rooibos infusion, taking into account variation caused by production seasons (2009, 2010, and 2011) and quality grades (A, B, C, and D), were determined for samples (n = 114) from different geographical areas and producers. The major phenolic constituents were isoorientin and orientin (>10 mg/L), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 23 publications
0
38
0
Order By: Relevance
“…Artificial rooibos infusions were prepared using the most abundant and available polyphenols naturally present in this beverage based on HPLC analysis of the infusions according to the method described by [24,33]. Stock solutions (2.0 mM in pure methanol, stored at −20 °C) of the polyphenols were prepared prior to their combination in the artificial infusions, representing green and fermented rooibos.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial rooibos infusions were prepared using the most abundant and available polyphenols naturally present in this beverage based on HPLC analysis of the infusions according to the method described by [24,33]. Stock solutions (2.0 mM in pure methanol, stored at −20 °C) of the polyphenols were prepared prior to their combination in the artificial infusions, representing green and fermented rooibos.…”
Section: Methodsmentioning
confidence: 99%
“…The effectiveness of these glycosylated polyphenols against reactive radical species that are directly involved in causing oxidative stress within living organisms remains unknown [32]. Recently, Joubert et al [24,33] have reported the oxygen radical scavenging capacities of rooibos infusions and extracts, using fluorescence detection (ORAC-FL). However, the antioxidant quality and the contribution of the glycosylated polyphenols to that anti-peroxyl radical scavenger ability of natural rooibos infusions are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As the benefits may be mediated through flavonoid interactions, it is important to note that higher grades are associated with higher flavonoid concentrations (Joubert, et al, 2012). When assessing different grades of rooibos for flavonoid content, higher levels of the following flavonoids: aspalathin, isoquercetin, rutin, hyperoside, quercetin-3-O-robinobioside, were observed with higher quality rooibos (Joubert, et al, 2012).…”
Section: Rooibos (Aspalathus Linearis) Found In the Mountainous Areamentioning
confidence: 99%
“…When assessing different grades of rooibos for flavonoid content, higher levels of the following flavonoids: aspalathin, isoquercetin, rutin, hyperoside, quercetin-3-O-robinobioside, were observed with higher quality rooibos (Joubert, et al, 2012). Flavonoid content can also be altered through fermentation.…”
Section: Rooibos (Aspalathus Linearis) Found In the Mountainous Areamentioning
confidence: 99%
“…Food processing may also change their content. The orientin and isoorientin content of a ready-to-drink rooibos beverage showed a slight change as a result of pasteurization and storage, postulated to be due to the conversion of aspalathin to these compounds [110, 127]. Except for luteolin, there is very limited data on the characteristic metabolism and transportation of these flavone glucosides.…”
Section: Introductionmentioning
confidence: 99%